Drought stress effect on polyphenolic content and antioxidant capacity of cowpea pods and seeds. (30th October 2020) - Carvalho, Márcia; Gouvinhas, Irene; Castro, Isaura; Matos, Manuela; Rosa, Eduardo; Carnide, Valdemar; Barros, Ana
Abstract: Cowpea ( Vigna unguiculata L. Walp) is a protein‐rich grain legume with high adaptability to heat and drought and can be consumed during all stages of the plant development. Drought is a severe environmental stress with major impacts on plant development and productivity. This study main objective was to understand the effects of drought stress on polyphenolic content and antioxidant capacity in plant tissue at different stages of cowpea development. Four cowpea genotypes grown until the anthesis under well‐irrigate conditions and then were submitted to two watering regimens (0% and 75% of field capacity) for one week. Immature pods and seeds and dry seeds were collected, and polyphenolic content and antioxidant capacity were evaluated by spectrophotometry. In general, differences between genotypes, plant growth stage and treatments were observed. A variation of phenolic content and antioxidant capacity has been detected in all cowpea genotypes and plant tissues at different development stages. Immature pods showed the highest values in all the parameters evaluated, while the dry seed presented the lowest values. The samples submitted to drought stress showed a slight decrease in all the parameters evaluated compared to control samples being this decrease only significant in some parameters and growth stages. This study shows that drought stress did not significantly influence the quality of cowpea through phenolic content and antioxidant capacity.